Diverging shrub and tree growth from the Polar to the Mediterranean biomes across the European continent. (17th February 2017) - Pellizzari, Elena; Camarero, Jesus Julio; Gazol, Antonio; Granda, Elena; Shetti, Rohan; Wilmking, Martin; Moiseev, Pavel; Pividori, Mario; Carrer, Marco
Abstract: Climate warming is expected to enhance productivity and growth of woody plants, particularly in temperature‐limited environments at the northernmost or uppermost limits of their distribution. However, this warming is spatially uneven and temporally variable, and the rise in temperatures differently affects biomes and growth forms. Here, applying a dendroecological approach with generalized additive mixed models, we analysed how the growth of shrubby junipers and coexisting trees (larch and pine species) responds to rising temperatures along a 5000‐km latitudinal range including sites from the Polar, Alpine to the Mediterranean biomes. We hypothesize that, being more coupled to ground microclimate, junipers will be less influenced by atmospheric conditions and will less respond to the post‐1950 climate warming than coexisting standing trees. Unexpectedly, shrub and tree growth forms revealed divergent growth trends in all the three biomes, with juniper performing better than trees at Mediterranean than at Polar and Alpine sites. The post‐1980s decline of tree growth in Mediterranean sites might be induced by drought stress amplified by climate warming and did not affect junipers. We conclude that different but coexisting long‐living growth forms can respond differently to the same climate factor and that, even in temperature‐limited area, other drivers like the duration of snow cover might locally play a fundamental role on woody plants growth across Europe. Abstract : Climate warming is expected to increase plant productivity and growth especially in temperature‐limited environments; however, vegetation dynamics considering concurrently both shrubs and trees are still not well explored. We investigated, with a dendroecological approach, the growth trends and climate sensitivity of Juniperus communis L. and coexisting trees to better understand their responses to recent climate in three contrasting biomes, Polar, Alpine and Mediterranean, across the European continent. Shrub and tree growth forms revealed divergent growth trends in all biomes, with juniper performing better than trees at Mediterranean than at Polar and Alpine sites. The post‐1980s decline of tree growth in Mediterranean sites might be induced by drought stress amplified by climate warming and did not affect junipers. This study emphasizes that other climatic drivers, as drought or snow cover, in addition to temperature could play a fundamental role in defining future woody plant growth under the pressure of climate changes.